Respuesta :

Answer:

2x + 3y = 4

Step-by-step explanation:

The standard form:

Ax + By = C

So from the given form, arrange it to the standard form.

First, simplify the form by distribution.

y + 6 = -2/3(x - 11)

y + 6 = -2/3x + 22/3

Next, you make the fractions into whole by multiplying both sides by 3(this would eliminate all fractions).

(3)y + 3(6) = 3(-2/3x) + 3(22/3)

3y + 18 = -2x + 22

Now, arrange the "Ax" and the "C's".

3y + 18 = -2x + 22

2x + 3y + 18 = 22

2x + 3y = 22 - 18

2x + 3y = 4

Cheers!